Basel revisited: An Assessment of the Legitimacy and Effectiveness of the Basel Framework. (3rd July 2018) - Min, Jie
Abstract : The unprecedented growth and expansion of global trade and finance in the world today calls for a harmonized global rulemaking system more than ever to accommodate the increasingly intertwined economic ties among nations. However, critics often look at international lawmaking by "sub-national actors" and "regulatory networks of bureaucrats" with deep skepticism on the ground that it lacks accountability and legitimacy compared to lawmaking at the national level. The Basel Committee on Banking Supervision (BCBS) serves as a counterexample. BCBS has been the foremost runner in promoting a harmonized global standard for banking regulation to remove systemic risk and strengthen the banking system. Despite perceived "democratic deficit" in such an international lawmaking process, BCBS has successfully developed three banking regulatory frameworks since the 1980s, which have been widely adopted worldwide, ranging from the most developed economies to countries with less sophisticated financial systems. This article aims to assess the legitimacy and effectiveness of the Basel Framework through a systematic account of the dynamics between states at the international level and within each state domestically during different stages of its development. Section 1 introduces the background of the international financial system in the 1970s, which served as the stimulus of the subsequent creation of the Basel Accord. Section 2 discusses the motivation behind the creation of BCBS in the early 1980s and presents paradoxical views on the interest alignment among participating states. Section 3 examines the formulation of the Basel Accord at the transnational level and the efforts that were made to enhance the legitimacy and accountability of this piece of soft law. Section 4 reviews the implementation of the rules at the national level through comparisons between the initial members of the framework and new participants, along with a look at non-member states that have also been strongly influenced by the Basel Framework.